Göttinger Gutachten II: kirchenrechtliche Gutachten in den Jahren 1990 - 2000 ; erstattet vom Kirchenrechtlichen Institut der Evangelischen Kirche in Deutschland - Campenhausen, Axel, Freiherr von (Jus ecclesiasticum, 2002)
This volume contains the latest, previously unpublished reports made by the Institute for Ecclesiastical Law of the Protestant church in Germany. About half of the reports made by the Institute between 1990 and 2000 have been selected. Including the Jus Ecclesiasticum Volumes 14, 30 and 48, a total of more than fifty years of the Institutes work have been documented. The comments deal with basic problems which arise in practical church work. They touch on questions which have regained relevance after German reunification, in particular in the Eastern member churches and Länder and on questions concerning the relationship between the church and the law pertaining to the state churches.